Justifying the bored self: On projective, domestic, and civic boredom in Danish retail banking. (September 2022) - du Plessis, Erik Mygind; Just, Sine Nørholm
In the wake of the financial crisis, Danish retail bankers have experienced a marked increase in mundane administrative tasks, which do not conform to what they expect their work lives to be. Seeking to understand how the bankers cope with this, the paper conducts a qualitative inquiry into the identity work of Danish retail bankers, focusing on the ways in which they reconcile experiences of boredom with their work-identity. Drawing on pragmatic sociology, this reconciliation is conceptualized as individual justifications of boredom through different orders of worth. The paper identifies three justifications of boredom: (1) Projective boredom posits boring administrative tasks as unwanted and problematic. This justification is generally in line with currently dominant empirical and theoretical accounts of the financial sector and finds no justification for boredom, seeking, instead, to eliminate it. (2) Domestic boredom justifies the boring tasks as a duty performed by the humble and respectable banker, who is concerned with their status in the local community and whose sense of pride has been damaged by the many scandals in the sector. Finally, (3) civic boredom justifies boredom as a sacrifice made by the selfless banker who acts in the interest of the common good, understood as a more responsible, and less greedy, financial sector. Here, the meaninglessness of specific tasks is transcended in the service of a higher purpose, which helps the individual sustain an identity as a solidary professional.